The Impact of the Health Care Reform Plan on the Rate of Caesarean Section in the Educational Hospital: A Case Study - Mahnaz Afshari; Mehrak Pourmotahar; Zohreh Qavami Azad; Rasoul Corani Bahador; Maryam Radin Manesh (Shahid Sadoughi University of Medical Sciences, 2018)
Background: In recent years, the tendency of women to have C-section has increased, without enough knowledge about it and its side-effects. Vaginal birth promotion program is one of programs included in the health care reform plan which is an important step in promoting the awareness of vaginal birth. The aim of this study is to investigate the impact of the health care reform plan on C-section rates in one of educational hospitals in Tehran University of Medical Science. Methods: The present study was descriptive-analytic which was conducted in longitudinal and retrospective manner. Data were collected from 8510 deliveries through the patients' medical records in the span of three consecutive years, one year before implementing the health care reform plan and two years after its implementation. Calculations were done via Excel and SPSS 20 soft wares. Results: From the total of 2309 deliveries in 2013, (before implementing the plan), 69 percent of them had C-section and 31 percent had vaginal delivery. In the first year of the plan, from a total of 2989 deliveries, 70.8 percent had C-section and 29.2 percent had vaginal delivery and in the second year, from a total of 3212 deliveries, 71.3 percent had C-section and 28.6percent had vaginal delivery. The rate of avoidable C-sections in 2013, was 21.6 %, in 2014, 14.8 % and in 2014, 15 % .The execution of health care reform plan led to a 6.7 % decline rate in avoidable C-sections such as elective caesarians.(p = 0.001). Among the reasons for non-avoidable caesarians are, repeated caesarian, failure in delivery, and preeclampsia, respectively. Conclusion: Although this hospital did not succeed in reducing the rate of C-section, considering the causes for C-section, it could reduce avoidable caesarians like elective deliveries. Given that this hospital has a large number of critically ill patients referred from other centers for C-section, it has a high rate of C-section. Two important factors contributing to the execution of this program are, making the delivery room's space pleasant according to the birth center standards, and increasing human resources and professional and friendly obstetricians. Therefore, in order to promote vaginal birth a comprehensive planning is needed.